Biomarkers of Hepatic Fibrosis in Chronic Hepatitis C: A Comparison of 10 Biomarkers Using 2 Different Assays for Hyaluronic Acid. Issue 3 (March 2017) - Tanwar, Sudeep; Trembling, Paul M.; Hogan, Brian J.; Parkes, Julie; Harris, Scott; Grant, Paul; Nastouli, Eleni; Ocker, Mathias; Wehr, Klaus; Herold, Christoph; Neureiter, Daniel; Schuppan, Detlef; et al.
Abstract : Background: Advancing fibrosis is regarded as the most important factor when stratifying patients with chronic hepatitis C for retreatment. Goals: (1) To compare the performance of 10 biomarkers of fibrosis, including patented tests, among patients with chronic hepatitis C and treatment failure; and (2) to assess the impact on biomarker performance of using 2 different assays of hyaluronic acid (HA). Study: For 80 patients, liver histology (Metavir) was compared with biomarker scores using sera obtained within 6 months of liver biopsy (indirect biomarkers: AST:ALT ratio, APRI, Forns index, FIB-4, Fibrometer V3G; direct biomarkers: ELF, Fibrospect II, Hyaluronic acid-HA, Fibrometer V2G, Hepascore). Direct biomarker scores were calculated using 2 validated assays for HA (ELISA and radiometric). Results: Using the ELISA assay for HA to calculate the direct panels, all 10 of the biomarkers exhibited comparable overall discriminatory performance (unweighted Obuchowski measure, ordROC 0.92-0.94, P- value>0.05) except AST:ALT ratio and APRI (ordROC 0.86-0.88, P -value<0.05). For the detection of moderate (F2-4) and advanced (F3-4) fibrosis, the AUROC of Fibrometer 2G were significantly higher than AST:ALT ratio and APRI but none of the other biomarkers. Good correlation was observed between the 2 HA assays (intraclass correlation coefficient=0.873) with the ELISA assay exhibiting superior diagnostic performance (ordROC 0.92 vs. 0.88, P -value=0.003). Importantly, the performance of many of the direct biomarkers at their diagnostic thresholds was heavily influenced by the choice of HA assay. Conclusions: Although many biomarkers exhibited good diagnostic performance for the detection of advancing fibrosis, our results indicate that diagnostic performance may be significantly affected by the selection of individual component assays. Abstract : Supplemental Digital Content is available in the text.